Osteología craneal del género Philodryas (Serpentes: colubridae) - Lobo, Fernando (1994)
We studied the skulls of eleven species of Philodryas. The skull of Philodryas patagoniensis is described, and some characters that show interspecific variation are recognized. These characters are used for phylogenetic inferences. We obtained three trees using Hennig86. The pair of sister species wich is presented in the three cladograms is P. mattogrossensis - P. varius: in only ene tree: P. buroni - P. burmeisteri.